The Impact Study of Re-Measurement of Fishing Vessels Based at Tumumpa Coastal Fishing Port - Tidajoh, Irma Sesi; Luasunaung, Alfret; Kaparang, Frangky E.; Manoppo, Lefrand; Sumilat, Deiske A.; Mantiri, Rose O.S.E. (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2021)
Physical inspection of fishing vessels is part of the flow applied by the Directorate General of Capture Fisheries to verify and confirm the congruence of the actual dimension of the fishing vessel with the official document of fishing license. This inspection includes the calculation of the vessel size measured in Gross Tonnage (GT) which determine the amount of fishery retribution paid as Non-Tax State Revenue (PNBP) in the capture fisheries sector. The purpose of this study is to examine the size discrepancy due to mark down practices by re-measurement and to calculate PNBP based on mooring services at Tumumpa Coastal Fishing Port, Manado. A comparison method using a t-test is applied to investigate the difference between two measurements. Based on the test, there is a significant difference between written and actual measurements of GT which affects PNBP. Keywords: GT, PNBP, re-measurement, mark down, Tumumpa Coastal Fishing Port.